Strategy Architecture of Business Development at Toyota Learning Center - Galang Prakasa Yusuf Putra; Nimmi Zulbainarni; Asep Taryana (Pelopor Publikasi Akademika, 2025)
Toyota Learning Center (TLC) has the potential to grow further due to market demand. However, in 2023, Toyota Learning Center experienced a significant decline in profitability and a low client retention rate. This reflects the challenges faced by the Toyota Learning Center in maintaining business growth and profitability amid the ever-changing market dynamics. This study aims to analyze the competency gap using the Importance-Performance Analysis matrix, analyze internal & external factor and design the strategic architecture for the business development of the Toyota Learning Center. Based on the gap analysis results, there are 9 parameters related to the curriculum, training facilities, instructors, and business expansion in quadrant I that need to be prioritized (high level of importance but require performance improvement). From the results of internal and external analysis, simulation-based facilities and comprehensive development programs are resources that provide a sustainable competitive advantage. Partnerships with VR/AR technology suppliers are opportunities that need to be optimized, and content plagiarism by other companies is a threat that needs to be minimized. The Strategic Architecture is structured over the period from 2025 to 2030, grouped into three stages: strengthening competencies, business growth, and excelling performance, to achieve the vision and mission of the Toyota Learning Center as a provider of the best learning experience in the automotive and cross-industry sectors.